From Engagement to Advocacy: Analyzing the Impact of UserGenerated Content on Brand Equity in Evolving Digital Ecosystems - Arora, Muskaan; Verma, Jayender; Vashista, Arun (Cuestiones de Fisioterapia, 2025)
The seemingly ever-evolving landscapes of modern-day digital environments are today dominated by what is commonly referred to as ‘consumer-generated content,’ or UGC. This paper aims to analyze the dual effect of UGC on brand familiarity, brand commitment, and perceived quality three facets of brand equity. To contribute to filling this gap, this study draws from a survey of social media users and brand managers for a mixed-methods approach to offer an empirical understanding of UGC’s impact on consumer perception and behaviour.